Student Worksheets of Angle Relationships Based on Indonesian Realistic Mathematics Education - Alip Hidayati; Ibrahim (Universitas Pendidikan Ganesha, 2022)
Mathematics learning will get optimal results if the process is supported by the right facilities, one of which is student worksheets. This study aims to develop student worksheets based on Indonesian Realistic Mathematics Education on the material of angle relationships that are considered valid. This research is development research with a 4D model covering Define, Design, Develop, and Disseminate. The instrument used is a material and media expert validation sheet. The data obtained in this study are classified into quantitative data and qualitative data. Quantitative data in the form of an assessment scale for the validity of student worksheets were analyzed by converting them into qualitative data using an analytical technique formulated by Aiken and known as Aiken's V formula. The results showed that the student worksheets based on Indonesian Realistic Mathematics Education on the relationship between angles produced were considered valid by material experts with an average value of 0.88 and were considered valid by media experts with an average value of 0.94. The developed student worksheets have been assessed as valid by material experts and media experts. The student worksheets were revised based on input from experts until they were finally judged to be valid and feasible to be tested.